Cape Verde : Seventh Review Under the Policy Support Instrument-Staff Report; Staff ;Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cape Verde. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Seventh Review Under the Policy Support Instrument for Cape Verde. All assessment criteria were met with a margin, and all but three structural benchmarks were met. Growth is holding up at 4 percent in 2009, and inflation is low. The authorities have responded to the global crisis by accelerating their largely externally financed investment program and by tightening monetary policy. IMF staff recommends completing the seventh review and modifying year-end assessment criteria on net international reserves, nonconcessional external borrowing, and domestic borrowing.